When dividing variables that ave the same base, keep the base and subtract the powers.y^9/y^3 = y^(9 - 3) = y^6
The answer is y^6
Answer:
A=12
Step-by-step explanation:
A=12 cuz that is the waayy
Let
x----------> the first number
y---------> the second number
z--------> the third number
we know that
x+y+z=19-----> z=19-x-y------> equation 1
2x+4y+5z=72-----> equation 2
4x-y=12------> equation 3
substitute equation 1 in 2
2x+4y+5*[19-x-y]=72----> 2x+4y+95-5x-5y=72----> -3x-y=-23
3x+y=23------> equation 4
add equation 3 and equation 4
4x-y=12
3x+y=23
--------------
7x+0y=35--------> x=35/7----------> x=5
4x-y=12------> y=4x-12----> y=4*5-12----> y=8
z=19-x-y------> z=19-5-8----> z=6
the answer is
the numbers are
5
8
6
Answer:
D
Step-by-step explanation:
First, simplify the equation.
-3x+1<7
-3x<6
x>-2 (the sign flips because you are dividing by negative)
> means x is greater than -2 so the line will go towards the right.
Because the sign is >, the dot is open.